Sorvete com extrato hidrossolúvel de arroz: análise físico-química e sensorial - Cátia Regina Storck; Giane Engel Montagner (Universidade do Estado do Rio de Janeiro, 2020)
Introduction: As there are many people with lactose intolerance, new dietary preparations with good sensory aspects and free from this disaccharide need to be proposed, which would ensure these individuals' well-being and quality of life. Purpose: To develop an ice cream made with water-soluble rice extract. Method: Ice creams were produced replacing 50% and 100% of cow milk with water-soluble rice extract, in two flavors (strawberry and chocolate). The methods for developing this study were based on the physicochemical analysis of the ice cream and the sensory analysis, to establish the degree of acceptability of the product, as well as the preference on the part of the consumers. Results: Both the chocolate and the strawberry water-soluble rice extract ice creams had higher carbohydrate content and lower energy values, due to its lower protein and lipid content in comparison with cow milk ice cream. There was good acceptability; particularly, the 50% rice extract strawberry ice cream had no significant difference to the 100% cow milk ice cream, regarding preference. Conclusion: It is concluded that the water-soluble rice extract ice cream is a product with good nutritional characteristics and good acceptability. It can be considered an alternative for people with lactose intolerance.